Phenotypic analysis of a temperature sensitive mutant in the large subunit of the vaccinia virus mRNA capping enzyme - Shatzer, Amber N. (2008)
The heterodimeric vaccinia virus mRNA capping enzyme is a multifunctional enzyme, encoded by genes D1R and D12L. Published biochemical experiments demonstrate that, in addition to mRNA capping, the enzyme is involved in early viral gene transcription termination and intermediate viral gene transcription initiation. This paper presents the phenotypic characterization of Dts36, a temperature sensitive mutant in the large subunit of the mRNA capping enzyme (G705D), encoded by gene D1R. At the non-permissive temperature, Dts36 displays decreased steady state levels of some early RNAs, suggesting a defect in mRNA capping. Mutant infections also show decreased steady state levels of some early proteins, while DNA replication and post-replicative gene expression are absent. Under non-permissive conditions, the mutant directs synthesis of longer-than-normal early mRNAs from some genes, demonstrating that early gene transcription termination is defective. If mutant infections are initiated at the permissive temperature and shifted to the non-permissive temperature late during infection, steady state levels of intermediate gene transcripts decrease while the levels of late gene transcripts remain constant, consistent with a defect in intermediate gene transcription initiation. In addition to its previously described role in mRNA capping, the results presented in this study provide the first in vivo evidence that the vaccinia virus mRNA capping enzyme plays a role in early gene transcription termination and intermediate gene transcription.